REVALENCE AND GENOTYPIC DIVERSITY OF THE SYMBIOTIC BACTERIUM WOLBACHIA IN THE DROSOPHILA MELANOGASTER POPULATION OF NALCHIK - R. A. Bykov; Yu. Yu. Ilinskii; M. A. Voloshina; I. K. Zakharov (Вавиловский журнал генетики и селекции)
The symbiotic bacterium Wolbachia is widespread in natural Drosophila melanogaster populations. Its frequency in D. melanogaster populations is broadly variable from occasional individuals to total infestation. Six genotypes are recognized in this symbiont: wMel, wMel2, wMel3, wMel4, wMelCS, and wMelCS2. Two of them are ubiquitous: wMel and wMelCS. Others occur either in local areas or in laboratory stocks. In spite of the studies of Wolbachia occurrence in D. melanogaster populations of the world, the information of its prevalence and genotypic diversity in Eurasian populations is still scarce. We analyze the prevalence and genotypic diversity of Wolbachia in the natural D. melanogaster population of the city of Nalchik. It is shown that the genotypic composition of Wolbachia and its frequency in the population have remained stable for four years. Two genotypes are present in the population: wMel and wMelCS, the former being predominant. We found no other Wolbachia genotypes in the Nalchik D. melanogaster population.